Spent Coffee Ground and Its Derivatives as Soil Amendments—Impact on Soil Health and Plant Production - Yi Hu; Juan Li; Yiping Wu; Dongdong Zhang; Zhiyong Qi; Rui Yang (Agronomy)
Spent coffee ground (SCG) is a main byproduct of the coffee industry and has been revalorized as a source of value-added products. The direct application of SCG as a soil amendment has drawn much attention in recent years as a more environmentally sustainable option. In this work, a comprehensive review of studies on the agricultural application of SCG is presented. The aims of this review were (1) to summarize the impacts of raw SCG on soil health and to identify the factors limiting its direct soil use, (2) to outline methods that are often used to upgrade SCG for soil application, and (3) to highlight the potential of SCG and its derivatives as a biocontrol agent and biofertilizer. The results indicate that raw SCG could improve certain soil health attributes, but plant growth is often limited owing to its phytotoxicity and induced N immobilization. To eliminate phytotoxicity, composting, vermicomposting, and thermochemical treatments have been employed but to a limited extent. SCG and its derivatives may be used as biocontrol agents for weeds, soil-borne pathogens, and pests. Novel bio-organic fertilizers based on SCG have also been developed. Future research should focus on the long-term effects of SCG and its derivatives as soil amendments under real scenarios and the underlying mechanisms, particularly the soil–plant–microorganism interactions.